Weaponizing Women’s Bodies for Authoritarian Power: The Handmaid's Tale and Anti-Abortion Politics in the USA - Catarina Almeida, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
ABSTRACT: Since the United States Supreme Court overturned the Roe v. Wade decision in June 2022, the USA has faced a crisis in women’s reproductive rights that has intensified following Donald Trump’s reelection. This article asks why women’s bodies are instrumentalized to fulfil the political goals of authoritarian regimes. It explores the role that attacks on women’s reproductive freedoms play in Trump’s political agenda by using Margaret Atwood’s dystopia, The Handmaid’s Tale, as a cognitive map to understand the political instrumentalization of women’s bodies and its consequences for women. It considers the manipulation of religion and ideas of womanhood, family values, and sexual morality as means of reproductive coercion, and how the state surveils those who try to circumvent the law. The article also examines how the underminingof women’s bodily autonomy is fostered by socioeconomic divisions that marginalize and divide women, limiting resistance, and how the media disseminate propaganda that manufactures women’s consent to their own repression.